Impact of Slurry Composition on Properties of Cellular Alumina: A Computed Tomographic Study1 . Issue 10 (17th May 2017) - Betke, Ulf; Dalicho, Sebastian; Rannabauer, Stefan; Lieb, Alexandra; Scheffler, Franziska; Scheffler, Michael
Abstract : Fine‐pored, 45 ppi (pores per linear inch) alumina foams are prepared from ceramic slurries with varying contents of additives (deflocculant, binder) and solid loading following a standardized procedure. Rheological key parameters (yield stress, high‐shear viscosity) of the respective slurries are determined by approximation of the experimental flow curves with appropriate rheological models. The resulting ceramic foams are characterized by computed tomography (CT) followed by a morphometric analysis of the reconstruction volume data. The main scope of the work involves the development of a procedure to reliably define the binarization threshold during these morphometric calculations, which is based on the analysis of the differential course of the total porosity results from calculations performed at varying binarization threshold values ("differential thresholding"). A very good match of the CT porosity results with experimental data is achieved, despite the unfavorable CT voxel resolution to foam structure fineness relation. The CT evaluation results are finally correlated to the rheological properties of the respective slurries used in foam manufacturing. The dominant slurry composition parameters are the weight fraction of the ceramic powder and the binder concentration. Increasing binder and solid content result in an increased yield stress and viscosity of the respective dispersion and consequently in a decreased porosity and cell size of the finally manufactured cellular ceramic. Abstract : Fine‐pored, 45 ppi alumina ceramic foams are prepared by the Schwartzwalder method from the respective ceramic dispersions. For these, the slurry composition is varied and its influence on the rheological parameters is investigated. The resulting foams are characterized by micro computed tomography including a new approach for the void ↔ material segmentation. Finally, the µ‐CT results are correlated to the rheological parameters of the slurries used in foam preparation.